"Urea to Urea" Approach: Access to Unsymmetrical Ureas Bearing Pyridyl Substituents. Issue 7 (8th March 2022) - Kasatkina, Svetlana O.; Geyl, Kirill K.; Baykov, Sergey V.; Novikov, Mikhail S.; Boyarskiy, Vadim P.
Abstract: A protocol for the synthesis of unsymmetrical ureas substituted by pyridyl/quinolinyl moiety has been developed. This method concluded in metal‐ and base‐free reamination of N, N ‐dimethyl‐ N '‐hetaryl ureas with a wide range of aryl and alkyl amines. The isolated yields vary from 40 to 96% depending on the nucleophilicity of the amines. The scope of this method includes more than 50 examples. The reaction is not hindered by either donor or acceptor groups as well as diverse functionalities. The synthesis can be easily scaled to gram quantities. Theoretical calculations supported by experimental data allowed us to propose a plausible mechanism for the process. This reaction takes place through the intermediate formation of hetaryl isocyanate. Abstract :